Green Building in the midst of Pandemic - Wardani, Fitria Kusuma, S.Ars (Smart City, 2021)
The COVID-19 pandemic has highlighted the need for healthy buildings that can protect against the virus. The healthy building feature includes good air quality and ventilation, natural lighting, and green open space. The features are embedded in a green building design. The benefit of green building on the wellness of its occupants, combined with the unfavourable pandemic situation, should have had increased the green building’s popularity. However, throughout the pandemic in Indonesia, the green building remains unpopular. This research attempts to uncover how the market demand for green building is shaped, how the situation is during the pandemic, and how this issue benefits the future development of the green building. The analysis found that the public’s knowledge is the factor that can be further utilized in developing the green building.